1995
DOI: 10.2136/sssaj1995.03615995005900030003x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Soil Degradation and Soil Productivity Restoration and Maintenance

Abstract: In the Piedmont of the Southern Appalachian region, soil degradation is most often expressed by crop water deficit that limits crop yield in the warm season. To evaluate the nature of variability on these cropped lands, soybean [Glycine max (L.) Merr.] yield and associated soil characteristics were measured across the range of surface soil conditions in 40 farm fields. Factor analysis of the data permitted identification of variables responsible for most of the yield variability. Carbon in the surface soil was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 0 publications
2
48
0
5
Order By: Relevance
“…Although the amount of SOC accumulated within the first few cm may not represent substantive values quantitatively when compared to total C in the soil profile, it plays an important role in soil quality. Bruce et al (25) found that maintenance of SOC within the first few cm of soil is essential for improving infiltration and crop-available soil water on degraded Ultisols. An increase in SOC with no-tillage compared to other systems has been associated with greater return of crop residues (8), and/or lower soil organic matter decomposition (13).…”
Section: Resultsmentioning
confidence: 99%
“…Although the amount of SOC accumulated within the first few cm may not represent substantive values quantitatively when compared to total C in the soil profile, it plays an important role in soil quality. Bruce et al (25) found that maintenance of SOC within the first few cm of soil is essential for improving infiltration and crop-available soil water on degraded Ultisols. An increase in SOC with no-tillage compared to other systems has been associated with greater return of crop residues (8), and/or lower soil organic matter decomposition (13).…”
Section: Resultsmentioning
confidence: 99%
“…Por outro lado, nas camadas de 0,10-0,20 m e 0,20-0,30 m, nos dois anos agrícolas avaliados, não foram constatadas diferenças significativas entre os sistemas de preparo de solo. Resultados semelhantes foram obtidos por Tormena et al (1998) Bruce et al (1995), com apenas um revolvimento do solo pode-se perder a maior parte do incremento de matéria orgânica obtido com sistemas sem revolvimento do solo. Na superfície,…”
Section: Resultsunclassified
“…A long-term study could reveal significant variations in the chemistry of corn stover tissue as a result of residue management practices and impacts to soil properties. Additionally, despite the limited effect of rye on stover composition, the benefits on soil productivity of cover crops under conservation tillage practices should always be considered [29,30]. Furthermore, retention of rye in the field could reduce soil contamination on feedstock and cause microclimate interaction that affect water retention properties and soil heating properties in the spring.…”
Section: Rye and Corn Stover Management Effect On Biomass Compositionmentioning
confidence: 99%